Prospects for Using Entomopathogenic Nematodes to Control the Vine Mealybug, Planococcus ficus, in South African Vineyards - le Vieux, P.D.; Malan, A.P. (South African Journal of Enology and Viticulture, 2016)
In South Africa, the most common method of mealybug control has been the use of chemical insecticides. Entomopathogenic nematodes (EPNs) of the of the families Heterorhabditidae and Steinernematidae potentially can be used within an integrated pest management scheme to control Planococcus ficus, the vine mealybug, which occurs on all parts of grapevine, including the roots. When Steinernema yirgalemense was applied to the soil of two vineyards with P. ficus, contained in pierced Eppendorf tubes, buried at a depth of 15 cm in the soil, mortalities of up to 50% were obtained after 48 h. The persistence of S. yirgalemense, measured using codling moth larval mortality was found to be zero in one vineyard, while in the other it was 70%, 12 weeks after application. Tests were conducted to establish the production of scavenger deterrent factors by H. zealandica and S. yirgalemense. Of the cadavers that were presented six days after nematode infection, 49% of the H. zealandica- and 60% of the S. yirgalemense-infected cadavers were left intact. Olfactometry tests indicated a significant difference concerning the number of S. yirgalemense infective juveniles (IJs) that were attracted to damaged Vitis vinifera roots and P. ficus, indicating active movement of the IJs and the attractive ability of organic compounds produced by the roots. This study shows that EPNs, and specifically S. yirgalemense, have promising potential as biological control agents for the control of P. ficus soil populations, and investigates some influential factors affecting EPNs as biocontrol agents in the agro-ecosystem.